CONSUMER BEHAVIOR ANALYSIS IN UTILIZING SMAMGALOKA APPLICATION SMA MUHAMMADIYAH 3 JEMBER - Bakhtiar, Sony (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: The purpose of this study is to determine and analyze the factors that influence consumer behavior at SMA Muhammadiyah 3 Jember in their decision to use the SMAMGALOKA application to monitor their child's educational development. Method: This research method uses a qualitative descriptive approach. The sample in this study was 10 participants. The study was conducted using interview, observation, and literature study methods. The interview results were followed up with data reduction, presented, and conclusions were drawn. Results: The results of the study showed that only 1 out of 10 participants did not use and did not really need the application and the rest felt helped by the application. These results indicate that the SMAMGALOKA application has succeeded in providing features that consumers have needed in organizing education at SMA Muhammadiyah 3 Jember. Novelty: This research shows novelty in terms of school management's response in answering consumer complaints and needs by creating an android-based application that also functions as a school management information system.